Desenvolvimento de queijo minas frescal probiótico com teor reduzido de lactose - Back, Daniele (2011)
In recent years, there has been an increasing demand for foods with some functional property, being the dairy products the largest range of functional products manufactured on the market today. Nevertheless, a large part of the world population is restricted to the consumption of dairy by having a deficiency or absence in the production of lactase in the gut. Thus, this study aimed to develop a probiotic Minas fresh cheese with low-lactose content and evaluate their physico-chemical, sensorial and technological characteristics as well as the viability of probiotic bacteria during storage. Six cheese formulations (T1 to T6) were prepared with milk treated with lactase enzyme (β-galactosidase) at concentrations of 0,3, 0,6 and 0,9 g / L in reaction times of 12 and 24 hours, all of which added by 1% of probiotic culture (Lactobacillus acidophilus e Bifidobacterium sp.). Two other formulations, T7 and T8, were both developed without the addition of lactose and only T7 containing probiotic. The lactose was reduced more than 70% for all treatments added lactase, reaching 93,23% in the treatment with larger amount of enzyme. The physico-chemical evaluation showed that all the cheeses were developed in accordance with current legislation regarding the parameters of moisture and fat. It was observed that the acidity values were significantly lower (ρ <0,05) for cheese with less lactose content and for chesse without probiotic culture to the values found for the other treatments. Although the counts of Lactobacillus acidophilus were below the established minimum, the counts of Bifidobacterium sp. always remained above 106 CFU g-1, regardless of the amount of enzyme lactase added. In the analysis of instrumental texture, there were no significant differences (ρ> 0.05) among treatments for the parameters of firmness, cohesiveness and gumminess. In the sensory analysis, panelists found the taste more sweet and less acid in the sample with higher hydrolysis of lactose, and found no difference in texture compared to controls. Based on the results obtained, it can be said that the enzyme lactase effectively reduced the lactose content in the developed cheeses, and did not change the physico-chemical, sensorial and technological neither the probiotic viability, being a positive option for the dairy market, especially for being able to reduce lactose intolerance symptoms.